4 Four-dimensional left ventricular blood flow energetics independently predict adverse remodelling post st-elevation myocardial infarction. (May 2018) - Garg, Pankaj; van der Geest, Rob J; Swoboda, Peter P; Crandon, Saul; Fent, Graham J; Foley, James RJ; Dobson, Laura E; Musa, Tarique Al; Onciul, Sebastian; Vijayan, Sethumadhavan; Chew, Pei G; Brown, Louise AE; et al.
Abstract : Introduction: Myocardial infraction (MI) leads to complex changes in left ventricular (LV) haemodynamics. It remains unknown how four-dimensional (4D) acute changes in LV-cavity blood flow kinetic energy (KE) affect LV remodelling. We hypothesised that LV blood flow energetics is independently associated with adverse LV-remodelling. Methods: We recruited 69 revascularised ST-elevation MI patients. All patients underwent cardiovascular magnetic resonance (CMR) at 1.5 T within 48 hours and at 3 months. CMR included cines, early/late gadolinium enhancement and whole-heart 4D flow. CMR analysis included: LV volumes, infarct size (IS, %), microvascular obstruction (MVO, %), two-dimensional, retrospective valve tracking derived mitral inflow metrics and 4D KE components. KE was derived using novel, semi-automated method by using endocardial contours on short-axis cines to extract intra-cavity velocity profile. Adverse LV-remodelling was defined as increase in LV end-diastolic volume by 15%. Results: Thirteen (19%) patients developed adverse LV-remodelling. Demographics were comparable between patients with/without remodelling. Baseline CMR in adverse LV-remodelling-group showed significantly lower EF, LV KE, Systolic, A-wave, in-plane KEs and increased MVO (p<0.05). In stepwise-regression analysis, only acute MVO (beta=0.17±0.06, p<0.05) and acute A-wave KE (beta=−0.17±0.08, p<0.05) independently predicted adverse remodelling at 3 months. A regression-model comprising of acute MVO and A-wave KE had high predictive value for adverse LV-remodelling (area under the curve=0.82, 95% confidence interval=0.7–0.9, p<0.001). Conclusion: LV haemodynamic assessment by novel, semi-automated, 4D KE mapping adds incremental value to predict adverse LV-remodelling. A-wave KE and MVO size early after acute MI are independently associated with adverse LV-remodelling.